100 ideas for secondary teachers : literacy across the curriculum - Tyrer, Graham (b, 2018)
"As Ofsted says, Literacy is a shared responsibility across the curriculum in secondary schools. But for subject teachers and school leaders outside of the English department, this can seem a daunting task. '100 Ideas for Secondary Teachers' contains all sorts of strategies and ideas for ensuring that pupils are developing competency in reading and writing in every subject, from maths to PE, without putting pressure on teachers' time and resources. The perfect quick-reference pocket book, this collection of creative and original ideas from English expert Graham Tyrer has something for everyone, ensuring all teachers and school staff are able to support students in gaining confidence in literacy."--
JHS
Text in English
Keywords: English language -- Study and teaching (Secondary) -- Great Britain; Language arts -- Correlation with content subjects -- Great Britain; Literacy -- Great Britain